Analisis Strategi, Jenis dan Efektivitas Sumber Belajar Berbasis Kearifan Lokal dalam Pembelajaran Tematik SD pada Pendekatan Etnosains - Eriyana Ernandhita Pratiwi; Oktaviana Sulis Rahmadani; Anindita Yogi Pertiwi; Muhammad Wisnu Wirayudha; Shelvia Rizka Saputri; Sri Marginingsih; Taufik Muhtarom (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the strategies, types, and effectiveness of local wisdom-based learning resources in thematic learning at the elementary school level using an ethnoscience approach. The research method employed is a Systematic Literature Review (SLR) based on 20 scholarly journal articles indexed in Google Scholar, retrieved using the Publish or Perish software. The literature selection process follows the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, which includes identification, screening, eligibility, and inclusion phases. Data analysis was carried out using thematic and comparative synthesis techniques to extract patterns regarding instructional strategies, types of local wisdom integrated, and the effectiveness of their application. The findings indicate that the integration of local wisdom—such as folktales, traditional games, regional songs, and cultural practices—significantly enhances learning outcomes (by 30–35%), student engagement, and critical thinking skills. Furthermore, the ethnoscience approach contextualizes learning and makes it more meaningful as it relates closely to students’ daily lives and cultural backgrounds. Therefore, local wisdom-based learning resources are highly relevant and effective in improving the quality of thematic learning in elementary schools.